1987
DOI: 10.1093/bja/59.11.1437
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Alfentanil in Children Undergoing Surgery

Abstract: Alfentanil pharmacokinetics and protein binding were determined in 20 children aged 10 months-6.5 yr. The data were compared with those from 10 adult patients. Eighteen children received a single i.v. dose of alfentanil 20 micrograms kg-1. The apparent volume of distribution (V beta) did not differ between the two groups. The degree of plasma protein binding was also similar in children and adults with mean free fractions of 11.5 +/- 0.9% (+/- SD) and 11.8 +/- 3.9%, respectively. There were marked differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…Protein binding was comparable (91.8-94.4%) in both groups. Similar protein binding (free fraction 11.5 ± 0.9%) was reported in children aged 10 months to 6.5 years [132]. Half-life was shorter and CL was higher compared with adults (11.1 ± 3.9 vs. 5.9 ± 1.6 mL/min/kg).…”
Section: Intravenous Alfentanilsupporting
confidence: 77%
“…Protein binding was comparable (91.8-94.4%) in both groups. Similar protein binding (free fraction 11.5 ± 0.9%) was reported in children aged 10 months to 6.5 years [132]. Half-life was shorter and CL was higher compared with adults (11.1 ± 3.9 vs. 5.9 ± 1.6 mL/min/kg).…”
Section: Intravenous Alfentanilsupporting
confidence: 77%
“…[66] Singleton et al [67] mentioned that mixed function oxidase enzymes (i.e. CYP) have greater activity in small children than in adults, resulting in a shorter duration of effect offentanyl.…”
Section: Agementioning
confidence: 99%
“…This diference has also been reported for other opioids. (16–18). In contrast, the only study including neonates, found that for the same dose of remifentanil, neonates aged <7 days needed 21 min to be extubated while older infants needed 6 min (6).…”
Section: Discussionmentioning
confidence: 99%